"Smart" Polymers: Physicochemical Characteristics and Applications in Bio-Separation Strategies. Issue 3 (3rd July 2018) - Hernández-Vargas, Gustavo; Ponce-Ponce de León, César Alejandro; González-Valdez, José; Iqbal, Hafiz M. N.
Abstract : In recent years, smart polymers (SPs), which are also referred to as bio-responsive polymers, have gained considerable attention as a unique class of polymers and their applications have been increasing significantly. These so-called "smart" polymers, either synthetic or biological, have been defined as "polymers designed to respond or undergo physical and structural conformational changes/rearrangement in response to slight changes in their surrounding environment". They are categorized as thermo-, pH-, electro- and magneto-responsive polymers. The advances in upstream bio-production stages and the high cost associated with downstream chromatographic techniques have pushed the development of new alternatives. In this context, the use of SPs, in combination with non-chromatographic technologies, represents a useful approach to the development of new downstream operation units. With the key scientific advancements, SPs have become the "next generation" of the bio-separation tool for eco-friendlier and cost-effective purification. This review describes the different characteristics and classifications of various "smart" polymers available for use in bio-separation strategy. Focus is also given to the recent advances in SP inclusion in the improvement of alternative non-chromatographic methods in downstream bioprocessings.